Mechanical behavior and shear band of a powder-metallurgy-fabricated CoCrFeMnNi high-entropy alloy during high strain-rate deformation - Wenshu Li; Bingfeng Wang; Xiaoxia Huang; Bin Liu; Jamieson Brechtl; Peter K. Liaw (Journal of Materials Research and Technology, 2022)
High-entropy alloys (HEAs) fabricated by powder metallurgy are considered to exhibit extremely-great potential application values in the field for high-speed impact deformation due to their uniform microstructures and compositions. The mechanical behavior of a powder-metallurgy-fabricated (PM) CoCrFeMnNi HEA was investigated at room temperature with strain rates ranging from 1200 s−1 to 2800 s−1. It was found that the serration behavior and shear localization of the alloy under dynamic conditions occurred. Results also indicated that the serrated flow took place in the PM CoCrFeMnNi HEA during mechanical deformation at high strain rates (>1000 s−1) and became more pronounced as the strain rate increased. Furthermore, it was determined that the yield-strength values of the PM CoCrFeMnNi HEA were sensitive to strain rates, where the values increased from 500 MPa to 700 MPa when the strain rates increased from 1200 s−1 to 2800 s−1. Shear bands with a width of about 20 μm were generated in the PM CoCrFeMnNi HEA after the shear stress reached a maximum value of 635 MPa, which corresponded to a nominal strain of about 8.71. Nanotwins and ultrafine-equiaxed grains with a diameter of about 150 nm also developed at the core of the shear band during deformation. The results revealed that the strength of the shear band was much higher than that of the matrix grain. Nanotwins in the shear band were composed of a single face-centered-cubic (FCC) structure with the twin plane of (1¯11¯), which could be formed via a rotational dynamic recrystallization (RDR).